Creating a Diploma Supplement Linked to Degree-Awarding Policies When the Curriculum Comprises Mostly of Elective Subjects - Yoshioka Tsuyoshi; Teruya Kensaku (Journal of Management Practices, Humanities and Social Sciences, 2020)
This study aims at defining a remodeled adjusted value for Learning Degree value Graph (LDG) and proposing a method to recalculate the Learning Degree (LD). The Diploma Supplement (DS) is an attachment to a degree certificate that enhances transparency by clearly indicating the contents acquired. DS for a curriculum mostly is comprised of electives and cannot fairly represent student abilities. This study uses a DS creation method linked to degree-awarding policies—commonly called